Technology and Language: Improving Speaking Skills through Cybergogy-Based Learning - Satria, Dadi; Zamzani, Zamzani; Nurhadi, Nurhadi; Arief, Ermawati (Society of Visual Informatics, 2024)
Language learning in the Industrial Revolution 4.0 and Society 5.0 era is required to produce students with 21st-century skills by increasing the capacity and capability of using technology in learning. Technology-based learning, known as cybergogy, is a continuity of learning paradigms that previously applied the principles of pedagogy and andragogy in the learning process. As a new concept in learning, cybergogy is essential in improving 21st-century skills in the form of the 6Cs (Citizenship, Character, Critical Thinking and Problem Solving, Communication, Creativity, and Collaboration). Enhancing communication skills through cybergogy-based learning is a novelty that has not been done much and has become the focal point of research. This research, part of development research using the ADDIE model, employed a quasi-experimental design conducted in 3 senior high schools in Yogyakarta, representing one school per category, namely the lower, medium, and high categories, based on UTBK scores. A non-equivalent control group design involving an experimental and control class was applied. The results of this study, which showed a significant improvement in students' communication skills, especially speaking aspects, through blended learning, are of great significance. Therefore, it can be concluded that cybergogy-based language learning has proven effective in improving students' communication skills through blended learning.